PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PARIWISATA KOTA PADANG PANJANG - Sauqi Murtodo; Armida Silvia; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This study aims to examine the effect of work discipline and physical work environment on the performance of employees at the Padang Panjang City Tourism Office. This research is descriptive research. The population in this study were all employees of the Padang Panjang City Tourism Office. This study uses primary data. The analytical method used is multiple regression analysis using SPSS version 20. The results of this study indicate that 1) work discipline has a positive and significant effect on the performance of Padang Panjang City Tourism Office employees with a significance value of 0.038 <0.052) The physical work environment has a positive and significant effect on the performance of employees at the Padang Panjang City Tourism Office with a significance value of 0.031 <0.05 3) work discipline and physical work environment both have a positive and significant influence on the performance of the Padang Panjang City Tourism Office employees with a significance value of 0,000 <0.05.Keywords: work discipline, work environment and performance